Refugee and displaced women: 60 years of progress and setbacks - Susan Martin (Amsterdam Law Forum, 2011)
2011 marks the anniversary of two important events in refugee protection. In 1951, the United Nations adopted the UN Convention Relating to the Status of Refugees. Forty years later, in 1991, the Executive Committee of the Office of the UN High Commissioner for Refugees (UNHCR) adopted Guidelines on the Protection of Refugee Women. Since 1991, there has been both progress and setbacks in providing equal and effective protection to both male and female refugees. The article concludes that the gap between rhetoric and reality for women and girls is still very large. Following a brief discussion of the demographic profile of refugees, the article discusses issues related to legal protection, physical security, and social and economic rights for refugee and displaced women. The article call for renewed efforts to implement fully the various legal instruments and guidelines that set out norms and standards of protection for refugees generally and women and girls specifically and to ensure that refugee and displaced women are able to participate actively in decisions that affect them and their families.